2018
DOI: 10.1080/14397595.2017.1414765
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for abnormal hepatic enzyme elevation by methotrexate treatment in patients with rheumatoid arthritis: A hospital based-cohort study

Abstract: MTX-induced abnormal hepatic enzyme elevation in Japanese RA patients was associated with dosage and eGFR as nongenetic factors, and with ABCB1 3435C>T and ATIC 347C>G as genetic factors in this hospital-based cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A total of 862 citations were collected from electronic databases, and, after excluding duplicates, screening titles and abstracts, and reading full articles, a total of 39 articles were included. 8,9,26-62 The study selection process is presented in Figure 1. The main characteristics of studies are summarized in Additional file 1: Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 862 citations were collected from electronic databases, and, after excluding duplicates, screening titles and abstracts, and reading full articles, a total of 39 articles were included. 8,9,26-62 The study selection process is presented in Figure 1. The main characteristics of studies are summarized in Additional file 1: Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…8 Interindividual differences in susceptibility to adverse events are suggested to be due to genetic polymorphisms related to the capacity of transporters and enzymes that mediate the biotransformation and accumulation/elimination of MTX in the body. 9 Therefore, identifying predictors of MTX toxicity is important for the management of RA to achieve individualized treatment. Accumulating evidence suggests associations between gene polymorphisms and MTX toxicity in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TYMS 28bp VNTR ( Baggott et al, 1986 ), MTHFR 677C>T ( Berkun et al, 2004 ; Caliz et al, 2012 ; Berkani et al, 2017 ), MTHFR 1298A>C ( Berkun et al, 2004 ; Davis et al, 2014 ; Berkani et al, 2017 ), ATIC 347C>G ( Muralidharan et al, 2016 ; Hakamata et al, 2018 ), MTR A2756G ( Nikbakht et al, 2012 ) and MTRR 66A>G ( Dervieux et al, 2006 ) may be associated with MTX toxicity. A study of 273 Caucasian patients with RA treated with MTX for at least 6 months showed that there were no associations between TYMS gene polymorphisms and the toxicity of MTX treatment ( Swierkot et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in genes encoding transporters and enzymes mediating the biotransformation and elimination of MTX have been suggested as one cause of adverse events [ 7 ]. In fact, several studies have shown that two single-nucleotide polymorphisms (SNPs) (rs1891133 and rs1801131) in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene, which is involved in the intracellular MTX pathway, are associated with MTX toxicity [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%